The Now : Poems - Goldbarth, Albert (Pitt poetry series., 2019)
The Now describes the unique, and sometimes baffling, moment in which we live, a time defined by an immediate future of online wonderments, fake news, multiple personalities, data economy, gene modification, and the rest of the exciting-and-yet-ominous "technology culture," even as it's a time when the urge to memorialize the past--to sing elegiacally--seems more important than ever.